Evaluation of Work Posture Using RULA and REBA Methods and Ergonomic Intervention Design in a Brownies SME in Bogor - Novia Rahmawati; Purana Indrawan; Annisa Kartinawati; Derry Dardanella; Fattah Jati Pangestu; Aurelia Rafandita; Akhfas Zidan; Cinthya D. Masithoh; Desvita Anggraeni; Dyanchalenda H. Yunanto; Kaila F. Ocsadira; Najwa S. Nainggolan (Universitas Islam Raden Rahmat, Malang, 2025)
This study aims to analyze ergonomic conditions and occupational safety in one of brownies SME, particularly in activities involving raw material lifting, gas cylinder handling, and product packaging. The methods employed include RULA and REBA to evaluate working postures, as well as direct observation of environmental factors. The findings indicate that most worker activities fall into the medium to high risk categories, which may lead to MSDs. The RULA and REBA assessment scores indicated high ergonomic risk levels, with scores of 7 and 10 for the sack-carrying posture, 4 and 5 for the water gallon lifting posture, and 5 and 9 for the squatting posture during packaging, respectively. Workplace environmental factors were also found to be suboptimal, with poor cleanliness and sanitation that could endanger workers. As corrective measures, this study proposes the design of a multi-purpose handling trolley for transporting sacks and gas cylinders, along with an ergonomic table and chair to support workers during the packaging process. These interventions are expected to reduce injury risks, improve comfort and hygiene, and enhance worker productivity. Thus, the application of ergonomics and occupational safety principles is proven essential in creating a safe, healthy, and efficient working environment in small-scale food industries.